SAT0435 Profile and degree of hyperglycemia after the infiltration of intrarticular corticosteroids to patients with and without type 2 diabetes mellitus. (23rd January 2014) - Moya, P.; Rodriguez de la Serna, A.; Magallares, B.; Diaz-Torné, C.; Sarmiento, M.; Cόrica, E.; Castellví, I.; Geli, C.; Laiz, A.; Malouf, J.; Perez, A.; de Llobet, J.M.
Abstract : Background: Corticosteroids (CS) are widely used in medicine for the treatment of multiple processes. In rheumatology, infiltrations with corticosteroids are indicated to relieve pain and improve joint limitation. Adverse effects of corticosteroids such as hyperglycemia are well known; nevertheless the existing information about the effects of the intrarticular administration is very scanty. Objectives: The aim of this study was to define the profile and degree of hyperglycemia after intrarticular administration of triamcinolone acetonide to patients with and without type 2 diabetes. Methods: It was an observational study. Twenty-one patients were included (9 with and 12 without type 2 diabetes). All of them received an intrarticular infiltration of 40 mg of triamcinolone acetonide and 1 ml of mepivacaine in a knee or a shoulder. All patients received a glucometer in order to determinate the glycemias before and 2 hours after breakfast, lunch and dinner, the previous day and during the 6 days after the procedure. A descriptive analysis, including demographic and clinical data, and a comparative analysis of mean glycemic data were performed. The results were analyzed using the SPSS's v19.0 statistical package. Results: Patients without diabetes showed an increase of glycemic index 48 hours following the infiltration, whereas it wasn't observed in the diabetic patients. Likewise, we observed a statistically significant increase of the postprandial glycemia (167, 36±58, 39 vs 174, 25±69, 42mg/dl; p=0, 025) of the day of the infiltration and in the determinations before breakfast (111, 40±23, 71 vs 135, 77±62, 26 mg/dl; p=0, 008) and post lunch (152, 089±25, 9 vs 181±60, 63 mg/dl; p=0, 002) of the following day. Conclusions: Type 2 diabetic patients do NOT need an increase of antidiabetic treatment after the intrarticular administration of 40 mg of acetone triamcinolone, provided that they do not present glycemic alterations after 6 days of the infiltration. On the other hand, the non-diabetic patients, present an hyperglycemic moderate and autolimited effect, without clinical significance. References: Habib GS, Abu-Ahmad R. Lack of effect of corticosteroid injection at the shoulder joint on blood glucose levels in diabetic patients. Clin Rheumatol.2007;26:566–8. Conn HO, Poynard T. Corticosteroids and peptic ulcer: meta-analysis of adverse events during steroid therapy. J Intern Med. 1994;236:619–32. Blackburn D, Hux J, Mamdani M. Quantification of the risk of corticosteroid induced diabetes mellitus among the elderly. J Gen Intern Med. 2002;17:717–20. Disclosure of Interest: None Declared